Zeroing in on red blood cell unit expiry. Issue 12 (20th September 2017) - Ayyalil, Fathima; Irwin, Greg; Ross, Bryony; Manolis, Michael; Enjeti, Anoop K.
Abstract : BACKGROUND: Expiry of red blood cell (RBC) units is a significant contributor to wastage of precious voluntary donations. Effective strategies aimed at optimal resource utilization are required to minimize wastage. STUDY DESIGN AND METHODS: This retrospective study analyzed the strategic measures implemented to reduce expiry of RBC units in an Australian tertiary regional hospital. The measures, which included inventory rearrangement, effective stock rotation, and the number of emergency courier services required during a 24‐month period, were evaluated. RESULTS: There was no wastage of RBC units due to expiry over the 12 months after policy changes. Before these changes, approximately half of RBC wastage (261/511) was due to expiry. The total number of transfusions remained constant in this period and there was no increase in the use of emergency couriers. Policy changes implemented were decreasing the RBC inventory level by one‐third and effective stock rotation and using a computerized system to link the transfusion services across the area. Effective stock rotation resulted in a reduction in older blood (>28 days) received in the main laboratory rotated from peripheral hospitals, down from 6%‐41% to 0%‐2.5%. CONCLUSION: Age‐related expiry of blood products is preventable and can be significantly reduced by improving practices in the pathology service. This study provides proof of principle for "zero tolerance for RBC unit expiry" across a large networked blood banking service.